Influência da adição de cálcio nas propriedades de pastas geopoliméricas destinadas a cimentação de poços de petróleo - Ribeiro, Diego Brasil (2012)
Nowadays, the search for new technologies that are able to follow the upcoming challenges in oil industry is a constant. Always trying properties improvements of the used materials, looking for the best performance and greater life time. Besides the search for technologies that show an improvement of performance, the search for materials environmentally correct along the whole production process. In Oil well cementing, this search for new technologies passes through the development of slurry systems that support these requests and that are also environmentally friendly. In this context, the use of geopolymer slurries is a great alternative route to cementing oil wells. Besides having good properties, comparable to Portland cement slurries, this alternative material releases much less CO2 gas in the production of their root materials when compared the production of Portland cement, which releases tons of CO2. In order to improve the properties of geopolymer slurries has been added Calcium Oxide, as observed in other studies that slurries where the Calcium is present the values of compressive strength is greater. The addition has been realized based in the CaO/SiO2 molar ratio of 0.05, 0.10 and 0.15. Have been performed compressive strength tests, thickening time, rheology and fliud loss control test of the slurries, following NBR 9831, as well as the physical chemical characterization of XRD, SEM and TG. Has been observed in most of the tests the slurries follow a tendency until the ratio of 0.10, which inverses in the ratio 0.15. This behavior can be explained by two phenomena that occur simultaneously, the first one is the break of the polymer chains and a consequent increase in molucules mobility, which prevails until the ratio of 0.1, and the second is possible approach of the chains due to the capacity of the calcium ions stabilize the charges of two different aluminum. There is only one linearity in the mechanical behavior that can be attributed to the appereance of the C-S-H phase. Based on this, it is concluded that the phenomenon of breaking the polymer chains predominates until the ratio of 0.1, causing an increase of the filtrate volume, lower rheological parameters and increasing thickening time. From the ratio of 0.15 the approach of the chains predominates, and the behavior is reversed